Escola Infantil Canguru (1977-2005): um estudo a partir de memórias e documentos - Escobar, Vera Regina Bolsson (Universidade do Vale do Rio dos Sinos, 2010)
This survey, entitled “Infantile School Kangaroo (1977-2005): a study from memories and documents”, discuss about the history and the memory of this private educational institution, localized in the Porto Alegre/RS/Brasil. The research proves that since the foundation, the school focus on childhood education, specially on children with special necessities. This institution focus also on the teacher’s permanent formation. The survey was accomplished by school’s documents and through testimonies from people that have contribute to the construction process. The survey analysis the educational practices and its reach in terms formative. The testimonies put on evidence the care from the teachers to the children, the permanent teacher’s courses, giving to it’s a sufficiently meaning sense to the survey’s potential that emerges from material and circumstantial documents from people, pictures and practices observed in this institute.
Keywords: Infância; Educação infantil; Formação continuada.; Memórias documentadas; Childhood; Childhood education; Memories; ACCNPQ::Ciências Humanas::Educação